Crystal structure of (1,10-phenanthroline) (tetrafluorophtahlato) copper(II), [Cu(C8F4O4)(C12H8N2)2](C8H2F4O4), C40H18CuF8N4O8 - Zhang Jun; Liu Yuan-Ying; Ying Kun (Zeitschrift für Kristallographie - New Crystal Structures, 2012)
C40H18CuF8N4O8, triclinic, P1̄ (no. 2), a = 11.499(2) Å, b = 11.806(2) Å, c = 14.516(3) Å, α = 111.86(3)°, β = 101.90(3)°, γ = 95.54(3)°, V = 1756.8 Å3, Z = 2, Rgt(F) = 0.0390, wRref(F2) = 0.0796, T = 293 K.